HCI in Business, Government and Organizations: 10th International Conference, HCIBGO 2023, Copenhagen, Denmark, July 23–28, Proceedings, Part I - NAH, Fiona Fui-hoon (Institutional Knowledge at Singapore Management University, 2023)
This two-volume set of HCIBGO 2023, constitutes the refereed proceedings of the 10h International Conference on HCI in Business, Government and Organizations, held as Part of the 24th International Conference, HCI International 2023, which took place in July 2023 in Copenhagen, Denmark. The total of 1578 papers and 396 posters included in the HCII 2023 proceedings volumes was carefully reviewed and selected from 7472 submissions. The HCIBGO 2023 proceedings focuses in topics such as artificial intelligence and machine learning, blockchain, service design, live streaming in electronic commerce, visualization, and workplace design.